Scalable total synthesis of horsfiequinone A. Issue 15 (11th April 2018) - Zhan, Rui; Du, Shou-Zhen; Kuang, Fang; Chen, Ye-Gao
Graphical abstract: Highlights: A four-step total synthesis of horsfiequinone A. Gram-scale synthesis. Only one column chromatography purification is needed. Abstract: Starting from two commercially available substrates, methoxyhydroquinone and piperonyl alcohol, a scalable four-step total synthesis of horsfiequinone A was developed. The notable feature of the synthesis is the application of two continuous sequential transformations. Namely, the key aldehyde9 and horsfiequinone A were prepared via scalable Wittig/hydrolysis and Wittig/catalytic hydrogenation/oxidation sequences, respectively. Importantly, the synthetic route required only three recrystallizations and one column chromatography purification step.